Advanced Metal–Organic Frameworks-Based Catalysts in Electrochemical Sensors - Chen, Yana; Yang, Zhiquan; Hu, Huilin; Zhou, Xinchen; You, Feng; Yao, Chu; Liu, Fang Jun; Yu, Peng; Wu, Dan; Yao, Junlong; Hu, Ruofei; Jiang, Xueliang; et al. (Frontiers in Chemistry, 2022)
Developing efficient catalysts is vital for the application of electrochemical sensors. Metal–organic frameworks (MOFs), with high porosity, large specific surface area, good conductivity, and biocompatibility, have been widely used in catalysis, adsorption, separation, and energy storage applications. In this invited review, the recent advances of a novel MOF-based catalysts in electrochemical sensors are summarized. Based on the structure–activity–performance relationship of MOF-based catalysts, their mechanism as electrochemical sensor, including metal cations, synthetic ligands, and structure, are introduced. Then, the MOF-based composites are successively divided into metal-based, carbon-based, and other MOF-based composites. Furthermore, their application in environmental monitoring, food safety control, and clinical diagnosis is discussed. The perspective and challenges for advanced MOF-based composites are proposed at the end of this contribution.